Spatio-temporal dynamics and evolution o f landscape pattern in coastal areas of central region, Vietnam - M., Kappas; Linh, Nguyen Hoang Khanh (VNU Journal of Science: Earth and Environmental Sciences; Vol 28 No 4, 2012)
Abstract: